Pengaruh Sistem Informasi Logistik Terhadap Efisiensi Pengiriman Barang (Studi Kasus Pada PT XYZ) - Siti Sahara; Fadly Auliano Romadona (Universitas 17 Agustus 1945 Semarang, 2024)
PT XYZ is a company based in South Jakarta, focused on providing smart logistics solutions using Logistics Information Systems in its business. Researchers want to measure the influence of Logistics Information Systems on Goods Delivery Efficiency. In this research, the researcher used a quantitative descriptive research method using a questionnaire as a research instrument and distributed it to 15 users of the PT XYZ Logistics Information System using a simple random sampling technique in sampling. Results from this research show a relationship (R) of 0.816. The coefficient of determination (R Square) was obtained at 0.666. The calculated F value = 25.926 with a significance level of 0.001 < 0.05. The constant value (α) is 6.601, while the Logistics Information System variable value (b / regression coefficient) is 0.828. The tcount value is 5.092 > ttable 2.131. This means that there is an influence between the Logistics Information System variable (X) on the Goods Delivery Efficiency variable (Y).